Evaluación de nueve cultivares de fréjol phaseolus vulgaris l. colectados en la zona de palmales provincia de El Oro - Salvatierra Condoy, Ruber Alexander (2007)
At the Farm “San Vicente”, located in Palmales country, and during the winter rainy season of year 2007, it was studied the agronomic behavior of 9 bean cultivars collected in the area, and the following objectives were proposed: 1.- To evaluate 9 bean cultivars (Phaseolus vulgaris L.) collected in Palmales area; 2.- To study the characteristics of the essayed cultivars; 3.- To select the more productive cultivars on the basis of yielding. The collected and studied cultivars were: Chileno boca negra, Percal blanco, Mantequilla, Cocacho, Rayado, Panamito, Negro, Bayo bolón, and Sedita rosado. On field, the genetic material was planted in parcels, grouped in blocks or reapplications, according to the Design of Blocks completely at Random. The agronomic variables evaluated were: days at emergence; height of plant at flowering; days at flowering; days at physiologic maturity; number of nodes per plant; height of plant at harvest; number of pods per plant; number of grains per pod; weight of 100 seeds; yielding per plant; yielding per parcel and per hectare. Once the cultivar was established, it was fertilized with Potassium nitrate at a rate of 160 kg/ha, and later, at 30 days of age, it was added Potassium sulfate at a rate of 180 kg/ha. Aditional cultural labors were carried out: disinfection of seeds, control of weeds, plagues and diseases. The cultivars showed different growing behavior: Bushy (B) Percal blanco, Mantequilla and Cocacho. Semi-bushy (SB): Chileno boca negra and negro. Climber (C): Rayado, Panamito, Bayo bolón and Sedita rosado. The seeds collected from the cultivars presented a good germinative response, and the emergence of plantules occurred until the sixth day after seeding. The variante analyses and Duncan Test for the averages of treatments showed high significance for the variance of treatments in all the agronomic characteristics. From the view point of grain yielding, the variety Chileno boca negra was the most productive with 1.680 kg/ha, among the group of the Semi-bushy; the Panamito variety, in the group of indetermined growing, reached 1631 kg/ha; meanwhile in the Bushy group, the Cocacho variety gave the highest yielding with 1.028 kg/ha. However, these averages were mean to low, as compared with those other works carried out in the low región of El Oro Province.